RISK AND PROTECTIVE FACTORS FOR ABUSE AND NEGLECT IN DAILY CAREGIVING. (8th November 2019) - Yefimova, Maria; Pickering, Carolyn; Maxwell, Christopher; Puga, Frank; Sullivan, Tami
Abstract: The stress-process model suggests a variety of factors related to the stress-experience as important in the formation of outcomes including elder abuse and neglect (EAN). Multi-level modeling with days (n=831) nested within caregivers (N=50) was used to evaluate relationships between theoretically-based risk and protective factors and odds of EAN. Disruptions in the daily routine are a significant risk factor for abuse and neglect. Participating in a meaningful activity at least twice a day with the care recipient is a significant protective factor for neglect (OR=0.19; CI=0.06-0.64; p=0.01), but not abuse. Hypotheses that spending the full day together would increase the risk of EAN, and receipt of instrumental support and caregiver participation in self-care would decrease risk, were not supported. Findings demonstrate that the risk of EAN varies from day-to-day in the presence and absence of contextual factors. Moreover, abuse and neglect may have different etiologic pathways.